2003
DOI: 10.1046/j.1469-0691.2003.00706.x
|View full text |Cite
|
Sign up to set email alerts
|

Growth on blood agar discriminates Mycobacterium avium and Mycobacterium intracellulare

Abstract: Mycobacterium intracellulare and Mycobacterium avium (MAC) require specialized culture and identification procedures. To simplify the diagnosis, we inoculated reference strains, and 85 M. avium and 12 M. intracellulare clinical isolates, on egg-based and sheep blood agar. After 5 days of culture, there were significantly more colonies on sheep blood than on egg-based agar for M. avium (ratio: 250.5 +/- 209) but not for M. intracellulare (ratio: 0.44 +/-0.11). Using a ratio > or = 20, the sensitivity of the ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Recent data have indicated that mycobacteria are in no way particular regarding their manipulation in routine clinical microbiology laboratories. Concerning isolation, routine sheep blood medium sustains the isolation and growth of the vast majority of mycobacteria encountered in clinical microbiology laboratories, including M. tuberculosis, Mycobacterium avium, and Mycobacterium intracellulare (24,141,142), with the notable exception of M. leprae, which cannot be propagated outside animals (143) but can be cultured in the footpads of immunocompromised mice. In addition, sheep blood agar and sheep serum agar media have also been used to analyze in vitro susceptibility to antibiotics (144).…”
Section: Mycobacteriamentioning
confidence: 99%
“…Recent data have indicated that mycobacteria are in no way particular regarding their manipulation in routine clinical microbiology laboratories. Concerning isolation, routine sheep blood medium sustains the isolation and growth of the vast majority of mycobacteria encountered in clinical microbiology laboratories, including M. tuberculosis, Mycobacterium avium, and Mycobacterium intracellulare (24,141,142), with the notable exception of M. leprae, which cannot be propagated outside animals (143) but can be cultured in the footpads of immunocompromised mice. In addition, sheep blood agar and sheep serum agar media have also been used to analyze in vitro susceptibility to antibiotics (144).…”
Section: Mycobacteriamentioning
confidence: 99%